2023
DOI: 10.1186/s12985-023-02177-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of abruptly increased paediatric patients with Omicron BF.7 or BA.5.2 in Beijing

Lei Yu,
Congying Wang,
Xiaoyun Li
et al.

Abstract: Background The coronavirus disease 2019 outbreak has hit Beijing since mid-Nov, 2022, with soaring growth of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) among children. Therefore, it is vital to determine the clinical manifestations of epidemic SARS-CoV-2 strains in paediatric patients. Methods In this study, nucleic acid tests (NATs) for SARS-CoV-2 were performed in paediatric outpatients with symptoms of acute respiratory tract i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…6,[23][24][25][26] Several studies have reported the epidemiological features in pediatric populations and measured the immune responses in the general population after Omicron BA.5 infection. [27][28][29][30] However, there is limited research focusing on elderly populations affected by Omicron BA.5 and/or XBB infections. 31 Therefore, in this study, we were enrolled in this study between August and October 2022 in Jining, Shandong Province, China (Figure 1A and Table 1; Table S1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,[23][24][25][26] Several studies have reported the epidemiological features in pediatric populations and measured the immune responses in the general population after Omicron BA.5 infection. [27][28][29][30] However, there is limited research focusing on elderly populations affected by Omicron BA.5 and/or XBB infections. 31 Therefore, in this study, we were enrolled in this study between August and October 2022 in Jining, Shandong Province, China (Figure 1A and Table 1; Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the epidemiological features in pediatric populations and measured the immune responses in the general population after Omicron BA.5 infection 27–30 . However, there is limited research focusing on elderly populations affected by Omicron BA.5 and/or XBB infections 31 .…”
Section: Introductionmentioning
confidence: 99%